Solid State Lightening Component LED: Role in Modern Lightening Technology - Sharma, Babu Ram (Himalayan Physics, 2017)
An understanding of Light-Emitting Diode (LED) technology is an investment in future prosperity. This article tries to explain the development of LED and how the development of LED lightening technology became a superior business judgment for industrial lightening. The Himalayan Physics Vol. 6 & 7, April 2017 (115-118)